Pengaruh Dana Zakat Terhadap Pembangunan Manusia Di Indonesia - Mudita Sri Karuni (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
The problem of poverty in Indonesia is the manifestation of the powerlessness of the people in accessing state development outcomes. Meanwhile, the development outcome done by the government is only enjoyed by a handful of people because the resource is not equitably distributed. Therefore, the role of zakat is needed to give direct fund to redistribute the wealth, so that human development can be realized. This research aimed to give the empirical result on whether zakat has an influence on human development in Indonesia. This research used the Human Development Index (HDI) indicator as an analysis tool, such as life expectancy, mean year school, and income. Hypotheses testing conducted in 15 years (2004-2018). Data used in this study is secondary data collected by the documentation method. From the regression analysis of Ordinary Least Square (OLS), it is found that zakat can increase human access to health care, education, and can raise revenues. This study provided implication for governments, zakat institutions, and Muslim communities who are obligated to pay zakat, in order to synergize the optimization of zakat funds in Indonesia.